Tree growth traits and social status affect the wood density of pioneer species in secondary subtropical forest. Issue 14 (14th June 2017) - Chen, Lingxiu; Xiang, Wenhua; Wu, Huili; Lei, Pifeng; Zhang, Shengli; Ouyang, Shuai; Deng, Xiangwen; Fang, Xi
Abstract: Wood density (WD) is not only an important parameter to estimate aboveground biomass but also an indicator of timber quality and plant adaptation strategies to stressful conditions (i.e., windthrow, pests, and pathogens). This study had three objectives: (1) to compare WD among seven subtropical tree species; (2) to determine how tree growth traits may influence possible differences in WD between the pioneer and shade‐tolerant species; and (3) to examine whether or not WD differs by tree social status (dominant vs. suppressed trees) within species. To do this, 70 trees were destructively harvested. From each tree, disks at different stem heights were obtained and subjected to a method of stem analysis to measure whole tree level WD. The results showed that WD differed significantly among the seven species ( p  < .001). Their average WD was 0.537 g/cm 3, ranging from 0.409 g/cm 3 for Choerospondias axillaris to 0.691 g/cm 3 for Cyclobalanopsis glauca . The average WD of the four pioneer species (0.497 ± 0.13 g/cm 3 ) was significantly lower ( p  < .01) than that of the three shade‐tolerant species (0.589 ± 0.12 g/cm 3 ). The WD of the pioneers had a significant positive correlation with their stem diameter at breast height (DBH), tree height ( H ), and tree age, but WD had a significant negative correlation with relative growth rate (RGR). In contrast, the WD of the shade‐tolerant tree species had no significant relationships with DBH, H, tree age, or RGR. The dominant trees of the pioneer species had a higher WD than the suppressed trees, whereas the shade‐tolerant species had a lower WD for dominant trees than the suppressed trees. However, the differences in WD between dominant and suppressed trees were not significant. Taken together, the results suggest that classifying species into pioneer and shade‐tolerant groups to examine the effects of tree growth traits and social status could improve our understanding of intra‐ and interspecific variation in WD among subtropical tree species. Abstract : We investigated inter‐ and intraspecific variation in WD among seven tree species in the subtropical region of Jingzhou County, Hunan Province, southern China. And the results imply that influences of tree growth traits and social status on WD were more pronounced for early successional tree species than late successional tree species in subtropical China